Síndrome de Eagle en otorrinolaringología - Nazar S., Rodolfo; Naser G., Alfredo; Fullá O., Juan; Zamorano C. , Alvaro; Althausen K., Melanie (Revista Hospital Clínico Universidad de Chile, 2008)
Eagle syndrome is characterized by recurrent clinical symptoms like globus, dysphagia and odynophagia, which can be explain by an abnormal elongation of the Estiloid Apophysis or the calcification of the estilohioid ligament. It affects in equal proportion to men and women, being most common in people older than 50 years. Its importance is that it appears as a differential diagnosis compared with other causes of cervicofacial pain, being its election treatment, the surgical resection of the Estiloid apophysis. The following is a review of the literature and a clinical case of a 44 years old man, who consulted with a history of 6 months of odynophagia, foreign body sensation and cervicalgia. After the clinical, endoscopic and the complementary study of images evaluation, it was concluded that this was an Eagle Syndrome.